Blending students’ feedback in flexible teaching-learning - Anwar, Faisal (World Institute for Engineering and Technology Education, 2013)
The on-line students’ feedback collection platform at Curtin University, Perth, Western Australia is known as eVALUate. Four years’ data (2008-2011) from the eVALUate survey for an undergraduate civil engineering unit is considered in this study. In 2008, traditional teaching methods (teacher-centred) were used and the overall students’ satisfaction was found to be lower than university and faculty averages. Because of the students’ feedback, from 2009, traditional teaching methods were blended with flexible learning resources (e.g. Blackboard and i-lecture). The 2009 eVALUate survey data showed that the learning outcomes and the overall students’ satisfaction improved to the point where they exceeded the university and faculty averages. In 2010 and 2011, similar blended teaching methods were adapted and amended according to the constructive feedback received, and the validity and sustainability of the method were checked. The percentages of agreement consistently exceeded the university and faculty averages and interestingly, agreement with all the items in eVALUate was found above 80%. Students’ overall performance also improved significantly indicating that blending students’ feedback in teaching provides better learning outcomes.